SISTEM INFORMASI RAWAT JALAN PASIEN BPJS PADA RUMAH SAKIT - Fernando B Siahaan; Dede Awalludin (Jurnal Teknologi Informatika dan Komputer, 2018)
Registration of outpatient BPJS at Rumah Sakit IslamJakarta Pondok Kopi in its operational condition is obstacles thatis a long time in the registration process due to the large volumeof patient visit each day. So it takes a cient server basedinformation system that can support so as to produce betterservice. The purpose of this study was to provide an alternativemodel of outpatient administration of BPJS patients. The methodused in this study waterfall with stages analyze the needs ofsoftware, design, code generation, testing and support. Thediscussion by designing the system in the form of usecasediagrams, activity diagrams, sequence diagrams and ERD. Theconclusion of this study computerized system made for RSIJPKcan help overcome the problems in the process of registration ofpatients so that the time required to be faster.This electronic document is a â€œliveâ€ template. The variouscomponents of your paper [title, text, heads, etc.] are alreadydefined on the style sheet, as illustrated by the portions given inthis document.